Pengaruh Macam Pupuk Kandang dan Dosis Pupuk NPK Terhadap Pertumbuhan dan Hasil Tanaman Cabai Merah (Capsicum Annum L.) - Amar Kurniawan; Edy Kustiani; Saptorini Saptorini (Universitas Kadiri, 2022)
Red chili (Capsicum annuum L.) is a vegetable with high economic value. The need for red chili continues to increase along with the increase in population. The productivity of red chili plants is balanced fertilization between organic and inorganic fertilizers. This experiment was to determine the effect of the combination of manure and dose of NPK fertilizer on the growth and yield of red chili plants. The experiment was carried out from February to June 2021 on the agricultural land of the Faculty of Agriculture, Kadiri University, Kediri. The environmental design used was a two factor Randomized Block Design (RAK) and three replications. The first factor is the type of manure, consisting of 3 levels: from cow manure (P1), from chicken manure (P2), from goat manure (P3). The second factor is the dose of NPK fertilizer consisting of 3 levels: 11.2 g/bed (D1), 22.5 g/bed (D2), 45 g/bed (D3). The results showed that the interaction between the type of manure and the dose of NPK fertilizer was significant on the number of fruit at 99 DAP and fruit length at 85 DAP. Types of manure showed significant differences in the number of leaves at 35 and 42 DAP, plant height at 7, 14, 21, 35, 42 DAP, number of branches at 42 DAP, fruit weight, and fruit length at 85 DAP, and dry weight of red chili plants. The difference in the dose of NPK fertilizer has no significant effect on all observed variables Cabai merah (Capsicum annuum L.) termasuk sayuran bernilai ekonomis tinggi. Kebutuhan cabai merah terus meningkat seiring bertambahnya jumlah penduduk. Produktivitas tanaman cabai merah dilakukan dengan pemupukan yang berimbang antara pupuk organik dan anorganik. Percobaan ini untuk mengetahui pengaruh kombinasi macam pupuk kandang dan dosis pupuk NPK terhadap pertumbuhan dan hasil tanaman cabai merah. Percobaan dilaksanakan pada bulan Februari sampai Juni 2021 di lahan Fakultas Pertanian Universitas Kadiri, Kediri. Rancangan lingkungan yang digunakan adalah Rancangan Acak Kelompok (RAK) dua faktor dan 3 kali ulangan. Faktor yang pertama adalah macam pupuk kandang, terdiri atas 3 taraf: dari kotoran sapi (P1), dari kotoran ayam (P2), dari kotoran kambing (P3). Faktor kedua adalah dosis pupuk NPK terdiri atas 3 taraf: 11,2 gr/bedengan (D1), 22,5gr/bedengan (D2), 45 gr/bedengan (D3). Hasil penelitian menunjukkan adanya interaksi antara macam pupuk kandang dan dosis pupuk NPK nyata terhadap jumlah buah umur 99 HST dan panjang buah umur 85 HST terhadap jumlah buah umur 99 HST dan panjang buah umur 85 HST. Macam pupuk kandang menunjukkan perbedaan nyata terhadap jumlah daun umur 35 dan 42 HST, tinggi tanaman umur 7, 14, 21, 35, 42 HST, jumlah cabang umur 42 HST, berat buah dan panjang buah pada 85 HST serta berat kering tanaman cabai merah. Perbedaan dosis pupuk NPK tidak berpengaruh nyata pada semua variabel pengamatan.